Portfolio : Critical Selection : 2017-2018 - Garvey, Ciara; Parsons, Gregory (Kilkenny : Design & Crafts Council of Ireland, 2017)
Bennett, Roger ; Burke, Úna ; Butler, Anne ; Byrne, Edmond ; Byrne, Mike ; Cairns, Stuart ; Connellan, Julie ; Doherty, Jack ; Flynn, Liam ; Flynn, Sara ; Harron, Karl ; Healy, Pierce ; Hickey, Jennifer ; Hogan, Joe ; Lee, John ; Lowry, Alison ; McCrory, Michael ; Moore, Cecilia ; Murphy, Cara ; O'Briain, Stephen ; O'Byrne, Susan ; O'Connell, Eily ; Ó Dubhghaill, Coílín ; O'Kelly, Angela ; Sykes, Sasha ; Walsh, Joseph ; Watts, Grainne ; Zelouf and Bell
boek